Application of the anion-exchange resin as a complementary technique to remove residual cyanide complexes in industrial plating wastewater after conventional treatment - Chu, Jae Hun; Kang, Jin Kyu; Park, Seong Jik; Lee, Chang Gu (Environmental Science and Pollution Research, 2020)
Cyanide is highly toxic and must be destroyed or removed before discharge into the environment. This study examined the ability of commercial anion-exchange resins to remove residual cyanide complexes from industrial plating wastewater as a complement to conventional treatment. Cyanide removal experiments were conducted with various initial concentrations, reaction times, and temperatures, and the presence of co-existing anions. The maximum cyanide removal capacity (Qm) of the Bonlite BAMB140 resin is 31.82 mg/g and effectively removes cyanide from aqueous solution within 30 min. The cyanide removal by the resin is an endothermic process and is affected by the presence of anions in industrial plating wastewater. The relative competitiveness observed in this study was sulfate > nitrate > chloride. A mixture of 0.05 M NaCl and NaOH regenerates resin for continuous reuse for 5 cycles. The Bonlite BAMB140 resin was able to remove residual cyanide complexes from industrial plating wastewater, but the removal capacity of the resin was reduced by more than three times in batch (9.94 mg/g) and column (6349.12 mg/L) systems. Based on the results, the anion-exchange resins are expected to be used as a complementary technique to remove residual cyanide complexes in industrial plating wastewater after conventional treatment.
Keywords: Adsorption; Anion Exchange Resins; Anions; Cyanides; Hydrogen-Ion Concentration; Kinetics; Waste Water; Water Pollutants, Chemical; Water Purification; Anion-exchange resin; Complementary technique; Cyanide removal; Industrial plating wastewater; Residual cyanide complex